Nouvelle exploration sur le lexique arabe vernaculaire/semi-vernaculaire de Tunisie à l’époque moderne: L’apport de l’ouvrage bio-hagiographique al-Fatḥ al-munīr fī l-taʿrīf bi-ṭarīqat al-šābbiyya wa-mā rabbaw bihi al-faqīr de l’écrivain Muḥammad al-Masʿūd al-Šābbī (m. 1028/1618) - Meouak, Mohamed (Oriente moderno, 2024)
This study focuses on the analysis of lexical items, sentence structures, and sentence fragments in vernacular and semi-vernacular Arabic as found in a Tunisian bio-hagiographic work dating from the early 11th/17th century. The author of the text, Muḥammad al-Masʿūd al-Šābbī (d. 1028/1618), hailed from the Kairouan region, and his work is entitled al-Fatḥ al-munīr fī al-taʿrīf bi-ṭarīqat al-šābbiyya wa-mā rabbaw bihi al-faqīr. The research is structured into three main sections. The first is an introduction that outlines the context and objectives of the study. The second section provides biographical and historiographical information about the author and his text. The third section is dedicated to the presentation and analysis of vernacular and semi-vernacular Arabic material extracted from the work. In conclusion, the study argues that Tunisian bio-hagiographic literature from the 10th/16th and 11th/17th centuries represents a distinct historiographical genre characterized by frequent use of dialectal elements. As such, it offers valuable insights into the role of dialectal registers in shaping modern Tunisian historiography.